1980
DOI: 10.1063/1.440208
|View full text |Cite
|
Sign up to set email alerts
|

Surface segregation of a Pt–Au alloy: An atom-probe field ion microscope investigation

Abstract: An absolute composition depth profile of a dilute gold alloy of platinum is obtained with a true atomic layer depth resolution. At 600±20 °C, the top {001} layer Au concentration is found to be as high as 99±20% for a sample with a bulk gold concentration of 4.1±0.7%. The Au concentration decreases monotonically into the bulk, with a characteristic depth of about three atomic layers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
29
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…For the Ag-Au (62,69) and Pd-Au (68) alloys a number of experimental studies indicate that no surface segregation occurs, in contradiction with other experimental data for Ag-Au alloys (57,75,76,83,84), PdAu alloys (79), and Pt-Au alloys (81,85) as well as most theoretical models. This absence of segregation may be due to a lack of thermodynamic equilibrium (69) or substantial preferential sputtering of Au atoms from the surface (68).…”
Section: Predicting and Observing Segregationmentioning
confidence: 61%
“…For the Ag-Au (62,69) and Pd-Au (68) alloys a number of experimental studies indicate that no surface segregation occurs, in contradiction with other experimental data for Ag-Au alloys (57,75,76,83,84), PdAu alloys (79), and Pt-Au alloys (81,85) as well as most theoretical models. This absence of segregation may be due to a lack of thermodynamic equilibrium (69) or substantial preferential sputtering of Au atoms from the surface (68).…”
Section: Predicting and Observing Segregationmentioning
confidence: 61%
“…Among the Pd 3 X alloys with strong segregation energies, only Pd 3 W is known to have a stable phase at this 3:1 composition, 43,44 as also observed for Pt 3 Co and Pt 3 Ni alloys. We expect that such systems with a stable ordered phase at 3:1 ratio are more likely to be ordered.…”
Section: Resultsmentioning
confidence: 86%
“…22 The present results are in good agreement with the experimental work of Tsong et al, who investigated surface segregation trends in Pt-Au alloys by applying atom-probe field ion microscopy. 23 Hörn-ström et al also reported a strong surface segregation of gold in three different Pt-Au alloys containing between 2 and 90 wt % gold. The alloys were studied using Auger electron spectroscopy.…”
Section: Resultsmentioning
confidence: 94%